Cyrano de Bergerac opera in four acts - Cain, Heinrich 1854-; Domingo, Plácido 1941-; Radvanovsky, Sondra 1969-; Chacón-Cruz, Arturo 1977-; Gilfry, Rodney 1959-; Fournillier, Patrick; Znaniecki, Michał 1969-; Znaniecki, Michał 1969-; Comte, Isabelle; Palewicz, Bogusław; Mancini, Tiziano; Rostand, Edmond 1868-1918; et al. (Naxos, 2009)
Large-nosed poet Cyrano is unable to face his beloved Roxanne, so he feeds his beautiful verse to her through the handsome, but poetically inept, Christian
Program notes by David Patmore, synopsis, and biographical notes on the performers, in English with French and Spanish translations (23 pages : portraits) inserted in container
Keywords: Cyrano de Bergerac / 1619-1655 / Drama; Rostand, Edmond / 1868-1918 / Film adaptations; Operas; Cyrano de Bergerac / 1619-1655; Rostand, Edmond / 1868-1918; Drama; Feature films; Film adaptations; Nonfiction films; Films autres que de fiction